LABORATORY METHODS FOR DIAGNOSING UROGENITAL CHLAMYDIA - Kudratova Z. E.; Shamsiddinova M. Sh. (International Journal of Innovations in Engineering Research and Technology, 2023)
All laboratory methods of diagnostics of chlamydial infections can be divided into the following groups: cytological methods, culture methods of chlamydia diagnostics, serological methods, molecular genetic methods (PCR) [1,2].